Educational Game as a Part of Pedagogical Education - Babadzhanova Nargiza Rustamovna; G. Dj. Tosheva (Researchparks Publishing, 2023)
This article contains thoughts and opinions about the concept of game, its types and tasks, the effectiveness of using didactic games, and the types of educational games.